The effect of horizontal mergers, when firms compete in prices and investments - Massimo Motta; Emanuele Tarantino (University of Mannheim, Department of Economics, 2017)
It has been suggested that mergers, by increasing concentration, raise incentives to invest and hence are pro-competitive. To study the effects of mergers, we rewrite a game with simultaneous price and cost-reducing investment choices as one where firms only choose prices, and make use of aggregative game theory. We find no support for that claim: absent effciency gains, the merger lowers total investments and consumer surplus.Only if it entails suffcient effciency gains, will it be pro-competitive. We also show there exist classes of models for which the results obtained with cost-reducing investments are equivalent to those with quality-enhancing investments.
urn:nbn:de:bsz:180-madoc-428052
Keywords: K22; D43; L13; L41; 330; horizontal mergers; innovation; investments; network-sharing agreements; competition